1994
DOI: 10.1161/01.atv.14.7.1193
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation results in a redistribution of glycoprotein IV (CD36).

Abstract: To investigate the possibility that thrombin and/or other platelet activators change the platelet surface expression of glycoprotein IV (GPIV, CD36), we used a panel of five GPIV-specific monoclonal antibodies (OKM5, 5F1, FA6-152, 8A6, and F13) directed against different epitopes. All these antibodies bound to resting platelets in a concentration-dependent and saturable manner, as determined by flow cytometry of washed platelets. Thrombin (1 U/mL) induced an approximately twofold increase in the platelet surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 63 publications
1
24
1
Order By: Relevance
“…However, with thrombin in particular, agonist stimulation of platelets from WAS patients resulted in a defective capacity to activate, as measured by increased CD62P (P selectin, an alpha-granule protein) or CD63 (platelet lysosomal protein) expression. These proteins are normally translocated to the platelet surface with thrombin activation (McEver & Martin, 1984;Niewenhuis et al, 1987); ADP activation usually causes less translocation (Michelson et al, 1994). The reasons for the defective CD62/CD63 activation patterns in the WAS platelets are unknown, but they are consistent with the muted ability of these platelets to modulate GPIIbIIIa expression following agonist stimulation.…”
Section: Discussionmentioning
confidence: 98%
“…However, with thrombin in particular, agonist stimulation of platelets from WAS patients resulted in a defective capacity to activate, as measured by increased CD62P (P selectin, an alpha-granule protein) or CD63 (platelet lysosomal protein) expression. These proteins are normally translocated to the platelet surface with thrombin activation (McEver & Martin, 1984;Niewenhuis et al, 1987); ADP activation usually causes less translocation (Michelson et al, 1994). The reasons for the defective CD62/CD63 activation patterns in the WAS platelets are unknown, but they are consistent with the muted ability of these platelets to modulate GPIIbIIIa expression following agonist stimulation.…”
Section: Discussionmentioning
confidence: 98%
“…When intense platelet stimulation occurs, ␣ IIb ␤ 3 and CD36 are redistributed, and surface expression increases, corresponding to the membrane exposition of the intracellular granular pool. 16,17 Two additional proteins normally absent from the platelet surface, P-selectin (GMP-140 and CD62P), abundant in ␣-granules, and CD63, a lysosomal component, are exposed on the plasma membrane after secretion of granular contents. 18,19 At day 0, normal CD36 and ␣ IIb ␤ 3 epitopes were both correlated with the platelet size.…”
Section: Discussionmentioning
confidence: 99%
“…22 Expression of CD36 in heart was increased in mice fed a high-fat diet. 27 Michelson et al 28 demonstrated that thrombin activation increases the expression of CD36 on the surface of platelets. Recently, Han et al 29 reported that native and modified LDLs increased the functional expression of CD36 by using J774 murine macrophages.…”
Section: Discussionmentioning
confidence: 99%